Linne and Ringsrud's clinical laboratory science : concepts, procedures, and clinical applications - Turgeon, Mary Louise (St. Louis, Missouri : Elsevier Science, 2020)
Thoroughly updated and easy-to-follow, Linne & Ringsrud's Clinical Laboratory Science: Concepts, Procedures, and Clinical Applications, 8th Edition offers a fundamental overview of the laboratory skills and techniques you$1 (Bll need for success in the clinical laboratory. Author Mary Louise Turgeon's simple and straightforward writing clarifies complex concepts, and her unique discipline-by-discipline approach helps you build knowledge and learn to confidently perform routine clinical laboratory tests with accurate, effective results. Topics like safety, measurement techniques, and quality assessment are woven throughout the various skills. The new eighth edition also features updated content including expanded information on viruses and automation. It$1 (Bs the must-have foundation for anyone wanting to pursue a profession in the clinical lab.s